2018
DOI: 10.7150/thno.26758
|View full text |Cite
|
Sign up to set email alerts
|

Combination of NIR therapy and regulatory T cell modulation using layer-by-layer hybrid nanoparticles for effective cancer photoimmunotherapy

Abstract: The efficacy of combined near-infrared (NIR) and immune therapies for inhibiting tumor growth and recurrence has gained increasing research attention. Regulatory T cells in the tumor microenvironment constitute a major obstacle in achieving robust CD8+ T cell antitumor immunotherapy. In the present study, we designed a photoimmunotherapy-based strategy involving a combination of photothermal and photodynamic therapies, followed by Treg cell suppression, for eliciting an immune response with IR-780- and imatini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 49 publications
1
70
0
Order By: Relevance
“…Similarly, Tregs mediate the immunosuppression by inhibiting the activation and expansion of effector T cells, and their downregulation could be ameliorated by the use of NCs. In particular, Tregs can be actively targeted by using their specific markers, such as glucocorticoid-induced Tumor Necrosis Factor Receptor-related protein (GITR), or neuropilin-1 receptor by binding of tLyp1 peptide [145,146]. However, this therapeutic strategy needs to be further validated because Tregs instability could be associated with the onset of autoimmune disorders [147].…”
Section: Nanoimmunology and New Targetsmentioning
confidence: 99%
“…Similarly, Tregs mediate the immunosuppression by inhibiting the activation and expansion of effector T cells, and their downregulation could be ameliorated by the use of NCs. In particular, Tregs can be actively targeted by using their specific markers, such as glucocorticoid-induced Tumor Necrosis Factor Receptor-related protein (GITR), or neuropilin-1 receptor by binding of tLyp1 peptide [145,146]. However, this therapeutic strategy needs to be further validated because Tregs instability could be associated with the onset of autoimmune disorders [147].…”
Section: Nanoimmunology and New Targetsmentioning
confidence: 99%
“…Liu and co‐workers showed that PLGA nanoparticles encapsulating indocyanine green (ICG, a PTT agent) and imiquimod (an adjuvant) in combination with free anti‐cytotoxic T lymphocyte antigen (CTLA)‐4 (a checkpoint inhibitor) led to potent antitumor responses in mice with 4T1 triple negative breast cancer . In the same year, Kim and co‐workers developed a PLGA nanoparticle encapsulating IR‐780 iodide (an infrared dye) to enable photodynamic therapy (PDT) and antigen formation after tumor localization as well as imatinib (a chemotherapeutic drug for leukemia) to reduce the suppressive function of regulatory T cells . Overall, PLGA nanoparticles engender a range of therapeutic strategies by virtue of their facile incorporation and decoration of drugs, cytokines, antibodies, and other immunomodulatory agents.…”
Section: Nanoscale Materials For Immunotherapymentioning
confidence: 99%
“…In addition, the coadministration of anti-PD-1 peptide (AUNP12) and hollow gold nanoshell coencapsulated PLGA NPs with CpG has been proven to mediate the maturation of DCs in vitro and enable direct tumor necrosis in bilateral and lung metastatic 4T1 tumor-bearing mice [169]. The antibody-modified PLGA core was used to load the hydrophobic drug imatinib (IMT), which was developed as an inhibitor of tyrosine kinase and then manufactured as IR-780 and IMT codelivery PH-sensitive NPs, which showed a great capacity to stimulate an effective CD8 + T-cell antitumor immune response [170].…”
Section: Novel Biomaterials For Cancer Immunotherapy Lipid-based Biommentioning
confidence: 99%